Design engineers' perception of health and safety and its impact in the design process. Issue 1 (18th January 2016) - Morrow, Susan; Hare, Billy; Cameron, Iain
Abstract : Purpose: – The purpose of this paper is to consider design engineers' perception of health and safety and its impact on their behaviour during design activity. The study presents three types of design engineers each, exhibiting particular tendencies when faced with health and safety considerations during design. The discovery of these tendencies pose important implications for education and professional institutions and practical measures are suggested to help design engineers manage their tendencies to be more conducive to ensuring improved health and safety performance. Design/methodology/approach: – An exploratory design method was used – grounded theory, to include 13, in-depth, one-to-one interviews with design engineers, representing junior staff, middle and senior management. Findings: – The paper provides empirical insights about how designers think and behave when asked to consider health and safety issues during the design process. It identifies three group types of designers: doers, receivers and givers, who will exhibit their particular tendencies based on how they view and understand the term health and safety. Research limitations/implications: – The data obtained were from design engineers only, and therefore the research results may lack generalisability. Therefore, researchers are encouraged to test the proposed propositions. Practical implications: – The paper includes implications for those involved in the creation and development of designers e.g., educators and professional bodies. The data forms the basis for helping designers to manage their perceptions towards the term health and safety and thus, their tendencies exhibited in their behaviour. Originality/value: – This paper contributes to new understanding of designers' behaviour and considers the significance of how designers' views of health and safety will influence their behaviour.